EXERGO-ECONOMIC ANALYSIS OF MICROCHANNELS IN SINGLE-PHASE FLOW - ÖZDEMİR, MEHMED RAFET; YILMAZ, MUSTAFA (YILDIZ TECHNICAL UNIV, 2018)
With the increase of energy demand, many researchers tried to develop scientific approaches in order to design more efficient and environmentally friendly energy systems. Exergo-economic (thermoeconomic) analysis of a system or device is an efficient tool for evaluating the system in terms of the thermodynamic and economic aspects. In this parametric study, exergo-economic analysis of rectangular copper plain microchannels under single-phase flow conditions were investigated using de-ionised water. The exergo-economic performance was evaluated based on the relative cost difference and unit cost per product exergy tools. The channel aspect ratio effect on the unit cost per product exergy and relative cost difference was examined using three microchannel test sections with the same channel hydraulic diameter (D-h = 0.56 mm) and length (L = 62 mm) but different aspect ratios beta = 0.5, 2.56 and 4.94) under single-phase flow conditions. The results showed that the exergo-economic performances of the three microchannel test sections decreased as the net heat input increased over the experimental range. Moreover, the exergo-economic performance of test section 2 (beta = 4.94) was found to be greater than the exergo-economic performances of test sections 1 and 3 (beta = 0.5 and 2.56) at fixed flow rate and fixed net heat input case.
Keywords: Exergo-Economic Performance; Microchannels; Thermo-Economics; Single-Phase Flow; POWER-PLANT